Las unidades de economía popular y solidaria y su relación con la actividad económica territorial en el año 2010 - López Ocampo, Tatiana Elizabeth (2014)
The main objective of this thesis is to analyze the relationship between the People and Solidarity Economy and economic activity in the country using cross-sectional data from the 2010 Economic Census for twenty-four provinces of Ecuador. Specifically, the influence of Units Popular and Solidarity Economy (UEPS) as a percentage of total economic establishments on per capita income and the average provincial wage analyzes. The results indicate the existence of a positive and statistically significant relationship between the UEPS as a percentage of total economic establishments to the average wage of workers and negatively related to the average income of the economic establishments. In terms of public policy, fostering new and strengthening UEPS existing favors the development of the provinces and the welfare of their workers